Tri-element nanozyme PtCuSe as an ingenious cascade catalytic machine for the amelioration of Parkinson’s disease-like symptoms - Xu, Hongdang; Ding, Xin; Li, Lingrui; Li, Qing; Li, Zhiye; Lin, Hongqi (Frontiers in Bioengineering and Biotechnology, 2023)
Parkinson’s disease (PD), as the second most neurodegenerative disease after Alzheimer's, is become intractable with the increasing ageing globle popuation. The exploration of nanomedicine has broadened the opportunities for developing novel neuuroprotective therapies. Especially, polymetallic functional nanomaterials have been widely used in biomedicine field in recent years, exhibiting flexible and diversified functions and controllable properties. In this study, a tri-element nanozyme (PtCuSe nanozyme) has been developed with desirable CAT and SOD-like activities for the cascade scavenging of reactive oxygen species (ROS). Especially, the nanozyme is suitable for relieving nerve cell damage by removing ROS in cells, as well as mitigating the behavioral and pathological symptoms in animal models of PD. Therefore, this ingenious tri-element nanozyme may have potential in the treatment of PD and other neurodegenerative diseases.